Implementasi Media Audio Visual dalam Meningkatkan Aktivitas dan Hasil Belajar Pendidikan Agama Islam Siswa - Nurasia Hasibuan; Erawadi; Zulhammi (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
This study aims to improve the learning activities and outcomes of fifth-grade students at SDN 200509 Perkebunan Pulo Bauk, Padangsidimpuan, in the subject of Islamic Religious Education (PAI) through the use of Audio-Visual Media. Initial observations indicated low student engagement and achievement due to the predominant use of lecture and discussion methods, which were less engaging for students. As a solution, this study implemented Audio-Visual Media in the learning process. This research employed the Classroom Action Research method, consisting of cycles that include planning, action, observation, and reflection. The findings showed an improvement in learning outcomes. The students' initial average score was 70.91, with a mastery level of 65.71%. After implementing Audio-Visual Media, scores increased in each cycle. Cycle I reached an average of 80.05–84.2, Cycle II 80.42–80.71, and Cycle III 84.91–85.09. Thus, the use of Audio-Visual Media has been proven to enhance student engagement and learning outcomes in Islamic Religious Education, confirming the research hypothesis.